Epidermodysplasia Verruciformis: A Rare Case Report - Alshammari, Rasha (Cureus, 2020)
Epidermodysplasia verruciformis (EV) is an uncommon disorder that is transmitted in an autosomal recessive manner. It is characterized by increased susceptibility to human papillomavirus (HPV) infection, which presents with hypo- or hyperpigmented macular lesions, pityriasis versicolor-like lesions, and an early tendency to transform into skin cancer. We present a case of a 36-year-old female with complaints of asymptomatic, multiform lesions over the face, neck, chest, and upper arms. Histopathology was suggestive of EV, and our patient was given oral isotretinoin 20 mg/day and advised strict photoprotection.